Writing in the workplace - Swann, David; Boland, Michael; Video Education Australasia (Australia : Video Education Australasia, 2007)
This engaging program provides the student with an overview of the purpose and advantages of writing as a medium and the advantages and disadvantages of writing compared with speaking. By focusing on a melodramatic case study of fictional restaurant manager Jason and his staff at Larder Restaurant, the program works through the steps to achieve success in workplace writing
Title from title screen
Executive producer : Mark McAuliffe ; camera : Peter Zajharov ; editor : Paul Suttherland ; senior producer : Richard Leigh
Keywords: Business writing; Business communication